Persuasive Approach to Terrorist Organization Members through the Welfare and Investment of National Values - I Ketut Widhiarto (Faculty of Law, Universitas Lampung, 2022)
Eradicating members of terrorist organizations is not limited to actions such as prison sentences. However, it can be a persuasive approach through welfare and the installation of national values. This right attempts to help terrorists understand and return to the teachings of the Indonesian Constitution and the Unitary Republic of Indonesia. To address the nature, characteristics, motives, and objectives of terrorism, this research formulated the concept of a persuasive approach to members of the Jemaah Islamiyah (JI) terrorism organization based on Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism. This paper also emphasizes the concept of deradicalization through a persuasive approach based on law Responsive to JI members involved in criminal acts of terrorism. This study employs a qualitative approach that is analyzed descriptively and normatively. According to the findings of this study, the essence of terrorism is an activity that causes unrest in people while masquerading as religion and has various characteristics and motives. Law enforcement is holistic, comprehensive, and long-term, both through a repressive legal approach model. The process of a repressive legal approach through the criminal justice system, in which the deradicalization process is expected to reform a terrorism prisoner from radical to moderate while in prison while serving a criminal sentence